ANALISIS KECELAKAAN LALU LINTAS DAN PENANGANAN DAERAH RAWAN KECELAKAAN JALAN AHMAD YANI (RUAS KM 17 – KM 36) KOTA BANJARBARU - Lestari, Utami Sylvia; Anjarsari, Renty Ika (Lambung Mangkurat University Press, 2020)
Traffic accidents are a problem that requires serious handling. Human factors (driver), environment, vehicles and roads are some of the factors that cause accidents. For this reason, it is necessary to analyze the existing traffic accident data. The location of the road section studied is Jalan Ahmad Yani km 17 – km 36 Banjarbaru City. The purpose of this study is to identify the location and causes of road accidents in order to provide handling efforts in accident-prone areas and points. The analysis is carried out to identify areas and points prone to accidents (blackspots) by calculating the number of fatal accidents (TF) and the UCL (Upper Control Limit) limit value. From the results of data analysis, there are 2 vulnerable areas (blacksite), namely the Jl. A. Yani km 19 – km 20 and the Jl. A. Yani km 21 – km 22. Furthermore, 8 road points were identified as Accident Prone Points (Blackspot). The accident-prone point that has the highest fatality rate is the point Jl. A. Yani km 19.25-19.50 Banjarbaru with TF = 10614.401 and UCL = 4523.506. The recommended traffic accident mitigation is to improve the awareness of road users in traffic by providing driving safety education and installing road facilities.